Characterization of indoor air particulate matter in selected elementary schools in Istanbul, Turkey - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2007)
The mass of indoor air particulate matter (PM10 and PM2.5) and its elemental concentration have been determined at five elementary schools in Istanbul, Turkey. Elementary schools were chosen because of the higher health risk associated with exposure to young children and the very high number of elementary school students currently being educated in Turkey. Results indicated that PM10 and PM12.5 maximum concentration limits determined by the World Health Organization were exceeded considerably in four schools located nearby a major road with high traffic density. Enrichment factor calculations obtained from the elemental composition results showed that Sb, Br, As and Zn were enriched considerably with respect to the Earth's crust, indicating an anthropogenic contribution to indoor air pollution levels in these schools.
Keywords: indoor air pollution; traffic-related; PM10; PM2.5; schools; children; TRACE-ELEMENTS; POLLUTION; OUTDOOR; PM2.5; PM10; EMISSIONS; MORTALITY; EXPOSURE; QUALITY